Coherent diffraction radiation as a source of radiation in far-infrared and terahertz range; JETP Letters; Vol. 98, iss. 3 - Shkitov D. A. Dmitriy Andreevich; Potylitsyn A. P. Alexander Petrovich; Naumenko G. A. Gennadiy Andreevich; Deng H. X.; Zhang J. B. (2014, 2014)
Title screen